Inhalation of tobramycin using simulated cystic fibrosis patient profiles. Issue 11 (1st May 2016) - Haynes, Alfred; Geller, David; Weers, Jeffry; Ament, Brian; Pavkov, Richard; Malcolmson, Richard; Debonnett, Laurie; Mastoridis, Paul; Yadao, Anthony; Heuerding, Silvia
Summary: Introduction: TOBI ® Podhaler™ is a capsule‐based drug‐device combination (tobramycin inhalation powder [TIP] 28 mg capsules via unit‐dose dry powder T‐326 Inhaler [Podhaler™]) developed for treatment of Pseudomonas aeruginosa infection in cystic fibrosis (CF). We explored how inspiratory flow profiles and mouth‐throat geometries affect drug delivery with the T‐326 Inhaler. Methods: Inspiratory flow profiles were recorded from 38 subjects aged 6–71 who had CF and varying degrees of lung function impairment. Ten of the inspiratory flow profiles were simulated in the laboratory using a custom breath simulator to determine delivered dose (DD) from the T‐326 Inhaler. In vitro total lung dose (TLDin vitro ) was measured using four anatomical throat models, ranging from a child to a large adult. Results: Aerosol performance was assessed across a range of inspiratory flow profiles. Mean DD ranged from 88.8% to 97.0% of declared capsule content. TLDin vitro ranged from 54.8% to 72.4% of capsule content between the flow profile/throat options tested, and the mean TLDin vitro across the range of flow profiles and anatomical throats tested was 63 ± 5%. Conclusions: Our findings indicate that the T‐326 Inhaler provides reliable drug delivery at flow rates likely to be achieved by a broad spectrum of patients with CF. Importantly, forceful inhalation was not required to achieve a robust TLDin vitro .Pediatr Pulmonol. 2016;51:1159–1167. © 2016 Wiley Periodicals, Inc.